SISTEM INFORMASI GEOGRAFIS DAERAH RAWAN BENCANA DENGAN FITUR PENDUKUNG KEPUTUSAN PENENTUAN LOKASI PEMBANGUNAN RUMAH DI KOTA KEFAMENANU - Budiman Baso; Leonard Peter Gelu; Anastasia Kadek Dety Lestari (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Kefamenanu City is located in East Nusa Tenggara (NTT) Province, precisely in North Central Timor Regency, this city borders land directly with the State of Timor Leste. The population density level in Kefamenanu city is relatively lower when compared to other regions in NTT, but by looking at the fact that most of the area is dominated by dry land and the increase in population growth rate that always increases every year, then in terms of providing land for housing locations will be a challenge for the TTU Regency Government. Determining the location of houses requires consideration of various aspects such as water availability, disaster vulnerability, public facilities, distance from trade centers, road conditions, transportation facilities, and land prices. This research aims to develop a Geographic Information System (GIS) that provides information related to disaster-prone areas and is equipped with a Decision Support System (SPK) using the Simple Additive Weighting (SAW) method. SAW method is used to help people in choosing housing locations based on the criteria they have. The results show that this system is effective in providing information and supporting decision making on housing locations that are safer and more comfortable, and can minimize potential disasters. In conclusion, the proposed system can be a valuable tool for local governments and communities in planning housing development in disaster-prone areas.